IT Governance Assessment at City Revenue Agency Using COBIT 5 Framework - Adhari, Muhammad Faresa; Setiawan, Johan (Universitas Bina Darma, 2024)
This study assesses the IT governance capability level at the Tangerang City Revenue Agency (BAPENDA) using the COBIT 5 framework to identify capability gaps and provide recommendations for improvement. Employing a qualitative descriptive approach, data were collected through interviews and observations to understand the current IT governance conditions against COBIT standards. The capability assessment revealed uneven levels across various processes. EDM04 (Ensure Resource Optimization) and MEA01 (Monitor, Evaluate, and Assess Performance and Conformance) were rated at Level 2, indicating that these processes are managed and controlled effectively. In contrast, APO07 (Manage Human Resources), BAI09 (Manage Assets), and DSS01 (Manage Operations) were assessed at Level 1, reflecting that these processes are operational but require substantial improvements to meet the target Level 3. The analysis highlights an urgent need to enhance IT governance, particularly in processes with lower capability levels. DSS01 (Manage Operations) was identified as the highest priority for improvement, based on the gap values and effort required for enhancement. The prioritization of process capability improvement in this study is guided by the principles of gap value and effort required for each process. Strategic enhancements in IT governance are crucial for the Tangerang City Revenue Agency to align better with best practices and achieve higher capability levels. Recommendations include implementing electronic-based applications, establishing Standard Operating Procedures related to performance targets and compliance, and improving IT human resources to enhance the effectiveness of IT service delivery and governance.